The Effect of the Financial Ratio on Company Value of Pharmaceutical Companies Listed in Indonesia Stock Exchange in 2013 -2016 - Eddy Winarso (Journal of International Conference Proceedings (JICP), 2018)
This study aims to determine the effect of financial ratios on the value of pharmaceutical companies listed on the Indonesia Stock Exchange (BEI) during the period 2013-2016, either partially or simultaneously. The financial ratios studied are: current ratio (CR), debt to equity ratio (DER), return on assets (ROA), total assets turn over (TATO) and price earnings ratio (PER). The population in this study is a pharmaceutical company listed on the Indonesia Stock Exchange (BEI) in 2013 to 2016. Research samples of 10 pharmaceutical companies obtained by purposive sampling technique. Data collection techniques used is documentation. Data analysis was done by panel data analysis technique. The results showed that partially ROA, TATO and PER variables significantly influence the firm value, while CR and DER have no significant effect. Simultaneously variable CR, DER, ROA, TATO and PER have an effect on to company value. CR, DER, ROA, TATO and PER variables can explain the value of companies in pharmaceutical companies listed in Indonesia Stock Exchange (BEI) in the year 2013-2016 for 82,65%. Keywords: Fundamental factors, financial ratios, current ratio (CR), debt to equity ratio (DER), return on assets (ROA), total asset turnover (TATO,) price earnings ratio (PER), and company value.